One big happy family - Day, Jamie (St. Martin's Press, 2024)
"The Precipice is a legendary, family-owned hotel on the rocky coast of Maine. With the recent passing of their father, the Bishop sisters--Iris, Vicki, and Faith--have come for the weekend to claim it. But with a hurricane looming and each of the Bishop sisters harboring dangerous secrets, there's murder in the air--and not everyone who checks into the Precipice will be checking out. Each sister wants what is rightfully hers, and in the mix is the Precipice's nineteen-year-old chambermaid Charley Kelley: smart, resilient, older than her years, and in desperate straits. The arrival of the Bishop sisters could spell disaster for Charley. Will they close the hotel? Fire her? Discover her habit of pilfering from guests? Or even worse, learn that she's using a guest room to hide a woman on the run. With razor-sharp wit, heart, thrills, and twists, Jamie Day's ONE BIG HAPPY FAMILY delivers a unique brand of summertime suspense"--